Survival after Aortic Valve Replacement with Bovine or Porcine Valve Prostheses: A Systematic Review and Meta-Analysis - Glaser, Natalie; Jackson, Veronica; Franco-Cereceda, Anders; Sartipy, Ulrik (The Thoracic and Cardiovascular Surgeon, 2019)
Background Bovine and porcine bioprostheses are commonly used for surgical aortic valve replacement. It is unknown if the long-term survival differs between the two valve types.We performed a systematic review and meta-analysis to compare survival in patients who underwent aortic valve replacement and received a bovine or a porcine prosthesis.Methods We performed a systematic search of Medline, Embase, Web of Science, and the Cochrane Library. Cohort studies that compared survival between patients who underwent aortic valve replacement and received either a bovine or a porcine bioprosthesis and that reported overall long-term survival with hazard ratio (HR) and 95% confidence interval (CI) were included. Two authors independently reviewed articles considered for inclusion, extracted the information from each study, and performed the quality assessment. We performed a meta-analysis using a random effects model to calculate the pooled HR (95% CI) for all-cause mortality. We did sensitivity analyses to assess the robustness of our findings.Results Seven studies published between 2010 and 2015 were included, and the combined study population was 49,190 patients. Of these, 32,235 (66%) received a bovine, and 16,955 (34%) received a porcine bioprosthesis. There was no significant difference in all-cause mortality between patients who received a bovine compared with a porcine bioprosthesis (pooled HR 1.00, 95% CI: 0.92–1.09). Heterogeneity between studies was moderate (55.8%, p = 0.04).Conclusions This systematic review and meta-analysis suggest no difference in survival between patients who received a bovine versus a porcine bioprosthesis after aortic valve replacement. Our study provides valuable evidence for the continuing use of both bovine and porcine bioprosthetic valves for surgical aortic valve replacement.
Keywords: aortic valve replacement; bioprosthesis; mortality; meta-analysis